2014
DOI: 10.1038/nrclinonc.2014.163
|View full text |Cite
|
Sign up to set email alerts
|

An update on PARP inhibitors—moving to the adjuvant setting

Abstract: Inhibition of poly(ADP-ribose) polymerase (PARP) enzymes is a potential synthetic lethal therapeutic strategy in cancers harbouring specific DNA-repair defects, including those arising in carriers of BRCA1 or BRCA2 mutations. Since the development of first-generation PARP inhibitors more than a decade ago, numerous clinical trials have been performed to validate their safety and efficacy, bringing us to the stage at which adjuvant therapy with PARP inhibitors is now being considered as a viable treatment optio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
228
0
3

Year Published

2015
2015
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 315 publications
(240 citation statements)
references
References 89 publications
2
228
0
3
Order By: Relevance
“…9 In cycling cells, if not repaired, SSBs tend to progress to DSBs that would be preferentially repaired through HR. 40,41 Consistent with our findings, CDK9-silenced cells exhibited an increased sensitivity to IR treatment that was intensified in the presence of a PARP inhibitor (Fig. 5).…”
Section: Discussionsupporting
confidence: 79%
“…9 In cycling cells, if not repaired, SSBs tend to progress to DSBs that would be preferentially repaired through HR. 40,41 Consistent with our findings, CDK9-silenced cells exhibited an increased sensitivity to IR treatment that was intensified in the presence of a PARP inhibitor (Fig. 5).…”
Section: Discussionsupporting
confidence: 79%
“…To investigate the question whether PARP inhibitors modulate chemosensitivity of Ewing sarcoma cells, we screened the efficacy of several anticancer drugs that are used in the clinic for the treatment of Ewing sarcoma (11) in the presence and absence of PARP inhibitors. We used suboptimal drug concentrations of PARP inhibitors and anticancer drugs that caused up to % 20% reduction of cell viability when used as single agents compared with untreated control (Supplementary Fig.…”
Section: Screening For Synergistic Drug Interactions Of Parp Inhibitomentioning
confidence: 99%
“…Indeed, Ewing sarcoma cells have been shown to be particularly sensitive to PARP inhibition (9,10). Several PARP inhibitors including talazoparib (BMN-673), niraparib (MK-4827), olaparib (AZD-2281), and veliparib (ABT-888) are currently under investigation (11).…”
Section: Introductionmentioning
confidence: 99%
“…These preclinical findings suggest that patients with BRCA1-associated MBC may show poor response to olaparib and illustrate the value of GEMM-ESC models of human cancer for evaluation of novel therapeutics. resistance | mouse model | breast cancer | BRCA1 | PARP P oly(ADP-ribose) polymerase (PARP) inhibition provides a promising therapeutic strategy for targeting homologous recombination (HR)-deficient tumors, such as breast cancer 1 (BRCA1)-mutated cancers (1). Indeed, clinical phase I and phase II trials have shown potent anticancer activity of small molecule inhibitors of PARP, such as olaparib, in patients with BRCA1-associated breast cancer (2,3).…”
mentioning
confidence: 99%